Research on Accessibility of Public Cultural Facilities Based on an Improved Model of 2SFCA—A Case Study of Suzhou City - Dai, Siyu (International Journal of Natural Resources and Environmental Studies, 2025)
Building a socialist cultural powerhouse is foundational to achieving the great rejuvenation of the Chinese nation. Accessibility to cultural facilities serves as a critical metric for assessing the equitable distribution of urban cultural resources. Leveraging public cultural facility POI data and ArcGIS software, this study employs an improved Gaussian Two-Step Floating Catchment Area (Ga2SFCA) model to evaluate the accessibility of cultural facilities across Suzhou City. By integrating clustering analysis of accessibility outcomes and supply-demand dynamics, the study identifies distinct accessibility patterns among demand units. Key findings include: (1) The enhanced Ga2SFCA model significantly improves evaluation accuracy. (2) While Suzhou City exhibits high overall accessibility to cultural facilities, spatial distribution remains highly uneven, with accessibility declining sharply from the urban core to peripheral areas. (3) Demand units are categorized into four clusters: High-Supply High-Demand High-Accessibility (HS-HD-HA) Units, High-Supply Low-Demand High-Accessibility (HS-LD-HA) Units, Low-Supply Low-Demand Low-Accessibility (LS-LD-LA) Units.